PENGARUH TAX MINIMIZATION, TARIF PAJAK EFEKTIF, DAN EXCHANGE RATE TERHADAP TRANSFER PRICING - Nungky Fitriyani Makhmudah; Chaidir Djohar (LPPM Universitas Bina Bangsa, 2023)
This study was conducted from a case that began with a notice of underpayment of the coke company The Coca-Cola Co with the United States (US) Internal Revenue Service (IRS) tax authorities and this study aims to test and obtain empirical evidence regarding the effect of Tax Minimization. , Effective Tax Rates and Exchange Rates for Transfer Pricing. This study uses a sample of primary consumer goods sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling method used in this research is purposive sampling method using eviews 9 for data analysis. Sources of data in this study are secondary data or quantitative data derived from the annual financial report (Annual Report) with a total sample of 65 observation data from 13 companies in the primary consumer goods sector with observations for 5 years. Based on the partial test with the T test, it states that tax minimization has a significant effect on transfer pricing, the effective tax rate has no significant effect on transfer pricing and the exchange rate has no significant effect on transfer pricing. Based on the simultaneous test with the F test, it states that tax minimization, effective tax rate and exchange rate simultaneously (simultaneously) have a significant effect on transfer pricing.